Using the annotating strategy to improve students' academic achievement in social studies - Zena T. Lloyd; Daesang Kim; J.T. Cox; Gina M. Doepker; Steven E. Downey (Journal of Research in Innovative Teaching & Learning, 2022)
Purpose – This experimental study aimed to examine the effects of annotating a historical text as a reading comprehension strategy on student academic achievement in an eighth-grade social studies class. Design/methodology/approach – A mixed-method design was used to collect quantitative and qualitative data sequentially. First, the authors collected quantitative data with a series of pre- and post-tests from all student participants during a six-week instructional time frame. Next, the authors collected quantitative and qualitative data with a survey from teacher and intervention group student participants. Quantitative data were analyzed to evaluate the mean differences in participants' test scores and survey responses. Finally, qualitative data from open-ended survey questions were transcribed and analyzed using an inductive approach to supplement the quantitative findings and develop a holistic picture of the participants' learning experiences. Findings – The results showed that the annotating strategy increased student engagement, reading comprehension and thus academic achievement in social studies. Annotating helped students visualize key points, break down complex texts and slow down when reading complex historical texts. As a result, it helped students focus, think critically and discourse to understand complex content. Research limitations/implications – The study was conducted with eighth-grade students in one middle school in South Georgia. Practical implications – The findings of this study provide evidence that the reading comprehension strategy of annotating is a valuable teaching and learning tool for daily use in social studies classrooms. Social implications – Educators must prepare students to use reading comprehension strategies such as annotating in all content areas and not only in a traditional academic setting. Originality/value – This study adds to the current body of research and undergirds reading comprehension strategies used to improve the learning outcomes in content other than reading.